Exploring a possible novel way of enterovirus cell-to-cell transmission through tunnelling nanotubes - Farabi, Sayma (My University, 2024)
Tunneling nanotubes (TNTs) are intercellular structures that facilitate direct communication between cells. Recent findings revealed that certain viruses can exploit these actin-based structures to facilitate direct cell-to-cell transmission, thereby evading immune system recognition. In this study, the role of TNTs in mediating cell-to-cell transmission of enteroviruses was investigated, providing insights into a novel mechanism of viral spread. This research aimed to investigate the potential role of TNTs in mediating the intercellular spread of Coxsackievirus A9 and Coxsackievirus B3. Reagents and methodologies were systematically optimized to investigate this novel mechanism. Enteroviruses would represent the first known non-enveloped human virus to exploit this mode of spreading. After virus infection in GMK cells, immunofluorescences and fluorescent small molecules were used to show infection, cellular morphology, formations of TNTs in infected and non-infected cells. To confirm intercellular connectivity via TNTs, split GFP technology was utilized in a way that when different cell populations, harbouring only fragments of GFP or sfCherry, connected to each other, a fluorescent signal could be observed. A significant increase in TNT formation following viral infection was demonstrated by the findings. Actin staining using Phalloidin confirmed the presence of actin filaments within these cellular protrusions, supporting their identification as TNTs. While some evidence indicated the presence of viral particles within these actin-containing structures, it was not conclusively determined whether the TNTs were open-ended and capable of facilitating viral transmission to neighbouring cells.
Keywords: enterovirus, fluorescent microscopy, green monkey kidney cells (GMK), split GFP, tunneling nanotubes